Validation of the I- and D-type epistemic curiosity scale among young Chinese children and implications on early curiosity nurture - Shuang Tang; Tianwei Xu; Lingyan Jin; Lina Ji; Qunlin Chen; Jiang Qiu (BMC Psychology)
Abstract Curiosity, an innate and intrinsic motivation to explore, makes vital contributions to learning in individuals of various ages. Epistemic curiosity centers on the drive to close information gaps and can be classified into joyous exploration and interest (I) and deprivation sensitivity (D) types. Each subtype is associated with different academic achievements, personality traits, emotions, and aspects of creativity. Building on the concept of epistemic curiosity in adults, the I- and D-type Epistemic Curiosity in Young Children (I/D-YC) scale was developed. The purpose of the present study was to validate the Chinese I/D-YC scale for preschoolers. Both exploratory factor analyses of data from 111 parents (Sample 1) and confirmatory factor analyses of data from 389 parents (Sample 2) indicated that the Chinese I/D-YC replicated the two-factor structure of the original scale. The scales’ convergent validity was examined with data from 189 parents (Sample 3) and 129 teachers (Sample 4), as its reliability and test–retest reliability was respectively examined with data from 389 to 82 parents (from sample 2). The results established the Chinese I/D-YC scale as a valid and reliable measure of epistemic curious behaviors in young Chinese children. Moreover, the cultivation of epistemic curiosity should weaken inhibition and this might enhance well-being and creativity and learning.